AB0022 STUDY OF FUNCTIONAL ORIENTATION OF B CELLS IN PHYSIOLOGY AND SJöGREN'S SYNDROME. (June 2019) - Boudigou, Marina; Grasseau, Alexis; Chriti, Nedra; Cornec, Divi; Pers, Jacques-Olivier; Hillion, Sophie; Pottier, Laetitia Le
Abstract : Background: Sjögren's syndrome (SS) is a chronic systemic autoimmune disease, characterized by mouth and eye dryness, due to irreversible destruction of glandular tissue by infiltrated lymphocytes. It is now well established that B cells play a key role in the physiopathology of SS. Indeed, B cells exhibit various signs of hyperactivity and produce excessive amounts of pro-inflammatory cytokines and immunoglobulins (Ig), especially IgG type-antibodies (Abs) (Kroese et al., 2014). Currently, it is suggested that the interleukin (IL)-21 (Wang et al., 2018) and IFNα (Yao et al., 2013), promote the generation of autoreactive IgG-producing plasma cells (PC). On the other side, some studies highlight the protective role of IgM producing cells in autoimmunity through enhanced efferocytosis and immune-regulatory properties (Ehrenstein and Notley, 2010). Objectives: This study aims to understand the influence of IL21 and IFNα on the B cell differentiation and the subsequent functional responses of the cells according to their maturation stage. Moreover, this will also enable a further understand of the contribution of these cytokines to the pathogenesis of SS. Methods: We established in vitro models to study the differentiation of different B cell subsets in a T-independent (TI) and T-dependent (TD) manner, under different cytokine stimulations. Naïve, switched memory, unswitched memory and CD27-negative memory B cells were isolated from peripheral blood of healthy controls (HC) and SS patients and thereby cultured in those different conditions. After three days of culture, the expression of surface markers and transcription factors was analysed by flow cytometry and molecular identity was further determined by transcriptional analysis. Additional functional assay was also performed to measure Abs and cytokine secretion. Results: First results on HC suggest that switched memory B cells differentiate into IgG and IgA-secreting plasmablasts (PB), when stimulated in a TI manner. This process is highly increased in presence of IFNα. Unswitched memory B cells mostly become PB able to secrete IgM and IL10. IL21 and IFNα oppose distinct effector functions. IL21 promote activation of B cells with an upregulation of the surface marker CD11c and T-bet transcription factor. Transcriptomic studies are still in progress to further define the molecular profile of those distinct effector B cells. Preliminary results on SS patients suggest that B cell differentiation is altered with a biased ratio between activated cells and PB. Conclusion: This work will allow us a better understanding of the heterogeneity of the distinct effector B cells and their involvement in SS pathogenesis. References: [1] Ehrenstein, M. R. & Notley, C. A. The importance of natural IgM: scavenger, protector and regulator. Nature Reviews Immunology10, 778–786 (2010). [2] Kroese, F. G. M. et al. B-cell hyperactivity in primary Sjögren's syndrome. Expert Rev Clin Immunol10, 483–499 (2014). [3] Wang, S. et al. IL-21 drives expansion and plasma cell differentiation of autoreactive CD11chiT-bet+ B cells in SLE. Nat Commun9, 1758 (2018). [4] Yao, Y., Liu, Z., Jallal, B., Shen, N. & Rönnblom, L. Type I interferons in Sjögren's syndrome. Autoimmun Rev12, 558–566 (2013). Disclosure of Interests: None declared